Distributional and Ecological Notes on the Halfbeaks of Eastern Gulf of Mexico, with a Provisional Key for Their Identifification - Contreras Balderas, Salvador; Lozano Vilano, María de Lourdes; García Ramírez, María Elena (1997)
Several fishes of the halfbeak genus Hyporhamphus occumng in the Mexican Gulf of Mexico and Caribbean Sea have been misidentified or confused in the literature. Most of it has centered around the taxonomic status of H. unifasciatus (including its synonym H. roberti), which is shown to comprise a complex of three species, H. unifasciatus, the recently described H. meeki, from the western Atlantic region, and an undescribed species from the eastern Pacific Ocean. Another eastern Mexico halfbeak is the freshwater form H. mexicanus. Using Banford and Collette (1993), we examined specimens from collections at UANL, UNAM, IPN, and ECOCH and have clarified the Mexican distribution of these species. We here report additional Mexican records of H. meeki, previously known only from United States waters and from the coast of Yucathn, clarify the distribution of H. unifasciatus, and provide the first marine record of the freshwater species H. mexicanus. A distribution map and keys for identification of the eastern Mexican species are provided.